Update on fungal keratitis in France: a case–control study - Olivier, Roxane; Knoeri, Juliette; Leveziel, Loïc; Negrier, Pierre; Georgeon, Cristina; Kobal, Alfred; Bouheraoua, Nacim; Baudouin, Christophe; Nordmann, Jean‐Philippe; Brignole‐Baudouin, Françoise; Merabet, Lilia; Borderie, Vincent (Acta ophthalmologica (Oxford, England), 2022)
Purpose To report an epidemiological update of documented fungal keratitis (FK) in a French tertiary ophthalmological centre from 2014 to 2018 in comparison with a previous period from 1993 to 2008. Methods Sixty‐two consecutive FK documented by microbiological corneal scrapings were compared with the 64 FK of the previous study. Amphotericin B and voriconazole eye drops were administered hourly. Population characteristics, clinical findings, aetiological organisms and treatments were analysed. Results The most frequently identified fungi were Fusarium (61%), Aspergillus (6.5%) and Candida (5%). Thirty out of 44 cases examined with in vivo confocal microscopy (IVCM) presented filaments. Ten required conventional cross‐linking, 9 therapeutic penetrating keratoplasty, and 2 enucleation. Risk factors significantly associated with the absence of response to medical treatment were patient age (p = 0.01), presence of a deep stromal infiltrate at presentation (p = 0.04) and high numbers of filaments in IVCM images (p = 0.01). The two populations were comparable in age, but not in sex ratio males/females (18/44 versus 37/26 in the previous study; p = 0.001). The frequency of contact lens‐associated infection increased from 35.5% to 71% (p = 0.0001) between the two periods. Since then, filamentous FK increased from 69% (44/64) to 95% (59/62) (p = 0.0001). A history of keratoplasty was less frequently reported during the last period (3.2% (2/62) versus 17% (11/64) of cases (p = 0.01)). A clear decrease in the frequency of therapeutic keratoplasty was noted from 39% (25/64) to 14% (9/62) (p = 0.02). Conclusion The frequency of filamentous keratomycosis is currently increasing. Elderly patients and the presence of numerous filaments in IVCM are associated with poor clinical outcomes.